Evaluation of Peer Counselling in the Elemntary School - Altmann, Dr. H. A.; Nysetvold, Ione; Downe, Allan (Canadian Journal of Counselling and Psychotherapy, 2011)
Recently, counsellors in a variety of settings have begun to make use of a relatively new concept know as "peer facilitation" or "peer counselling." The authors identify some of the evaluation instruments being used in peer counselling programs in the school systems along with some essential aspects of evaluation. The need for evaluation and research is indicated.